1994
DOI: 10.1002/mrc.1260321315
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the reactivity ratios, sequence distribution and stereoregularity of butyl acrylate‐methyl methacrylate copolymers by means of proton and carbon‐13 NMR

Abstract: The 400 MHz proton NMR spectra of butyl acrylate (BA)—methyl methacrylate (MMA) copolymers prepared by free radical polymerization in solution at 323 K were used for the determination of the reactivity ratios. The reactivity ratios rM and rB calculated by the error‐in‐variables method are 2.279 and 0.395, respectively. The methoxy region of the MMA proton signal resonance was found to be sensitive for MMA‐centred sequences and a new assignment is proposed. The coisotacticity parameter σBM was calculated using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 23 publications
3
36
0
Order By: Relevance
“…The composition was determined from the -O-CH 3 and -O-CH 2 -regions. [31] Size exclusion chromatography (SEC) was carried out using THF as an eluent at a flow rate of 1 mL Á min À1 . Two Polymer Laboratories PLgel 5 mm Mixed-C columns (300 Â 7.5 mm) and a PLgel 5 mm guard column (50 Â 7.5 mm) were used and calibrated with Polymer Laboratories narrow MWD polystyrene standards.…”
Section: Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…The composition was determined from the -O-CH 3 and -O-CH 2 -regions. [31] Size exclusion chromatography (SEC) was carried out using THF as an eluent at a flow rate of 1 mL Á min À1 . Two Polymer Laboratories PLgel 5 mm Mixed-C columns (300 Â 7.5 mm) and a PLgel 5 mm guard column (50 Â 7.5 mm) were used and calibrated with Polymer Laboratories narrow MWD polystyrene standards.…”
Section: Analysesmentioning
confidence: 99%
“…The fractions of monomer in the reaction mixture for optimal determination of the reactivity ratios were determined using the Tidwell and Mortimer criterion. [46] Initial estimates for the reactivity ratios were taken from Aerdts et al [31] The copolymer compositions for all experiments are shown in Table 3. Conversions were around 3.5%.…”
Section: Effect Of Cct On Reactivity Ratiosmentioning
confidence: 99%
“…The ␦ 5 and ␦ 6 showed only small downfield values because of the influence of the heteroatoms. In addition to these absorptions, the methine (O P CHO) absorbed at 41.6 ppm and the methylene (OCH 2 O) group at 35.6 ppm, while the CAO resonated at 174.4 ppm 4,24. In all these polyacrylates, the carbonyl carbons do not show any splitting, but the methylene carbons show splitting because of configurational effects(Fig.…”
mentioning
confidence: 99%
“…Furthermore, Aerts et al 9) found values of the apparent reactivity ratios of butyl acrylate/methyl methacrylate/ toluene system which differ from those obtained in bulk or in benzene, but as in the case of copolymerization carried out in benzene, both reactivity ratios are higher than those obtained in bulk. Considering that solvent effects are dependent on the characteristics of the solvent involved, and that benzene and toluene have similar polarity, this work describes the copolymerization of butyl acrylate with methyl methacrylate in benzonitrile.…”
Section: Introductionmentioning
confidence: 72%
“…2 also contains the monomer reactivity ratios values reported by Dube and Penlidis 8) for BA/MMA/ bulk, by Aerts et al 9) for BA/MMA/toluene and by Madruga and Fernández-García 7) for BA/MMA/benzene system. Since the BA/MMA behaves in a similar manner when the copolymerization is performed in benzene or in toluene and considering that both solvents have similar polarity, on the remainder, our analysis will be limited to the effect of two solvents: benzene and benzonitrile.…”
Section: Resultsmentioning
confidence: 94%